The Mineral Industry Of Other Areas Of South America - Ecuador - Travis Q. Lyday (The National Institute for Occupational Safety and Health (NIOSH), 1985)
During 1983, Ecuador's gross domestic product (GDP) decreased by a reported 3.3% in real terms, the second consecutive decline in the economy after more than a decade of growth generated mainly by petroleum export revenues. The slowdown was due, in part, to the effects of the world recession, lower foreign demand for oil, depressed world oil prices, and reduced demand and prices for Ecuador's traditional agricultural exports. Inflation accelerated to an estimated 55% annual rate. The sucre was devalued in March, for the second time in less than a 12-month period, by 27% after remaining unchanged during the previous decade. In addition, continuous adjustments were made every weekday, effectively devaluing the sucre another 30% by yearend. Ecuador's production of crude petroleum increased almost 12% in 1983 compared with that of 1982. Average daily production was 237,100 barrels per day (bbl/d), up from 211,300 bbl/d in 1982.